Nonoscillatory Properties of Fourth Order Nonlinear Neutral Differential equation - Mushtt, Intidhar Zamil; Hameed, Dunya Mohamed; Mohamad, Hussain Ali (Iraqi Journal of Science, 2023)
In this paper, the oscillatory and nonoscillatory qualities for every solution of fourth-order neutral delay equation are discussed. Some conditions are established to ensure that all solutions are either oscillatory or approach to zero as .  Two examples are provided to demonstrate the obtained findings.